Debate On Efforts to Extend the Presidential Term Limit During The Joko Widodo Administration from a Democratic Perspective - HENDRA, Hendra (Journal of Governance, Taxation and Auditing, 2025)
Since the amendment to the 1945 Constitution, the presidential term in Indonesia has been limited to a maximum of two terms. An interesting phenomenon has emerged in Joko Widodo's second term, with both pros and cons surrounding the idea of extending the presidential term to three terms. Some literature states that limiting the presidential term is one of the democratic indicators in preventing authoritarianism. While other opinions state that limiting the presidential term is considered undemocratic because it is not in line with the will of the people. Through a qualitative approach supported by literature studies, the author concludes that the idea of changing the presidential term limit is considered not contrary to democracy when viewed in terms of the will of the people in general elections. Still, suppose other factors such as the party system, the functioning of representative institutions, and the guarantee of the independence of the judiciary do not support the creation of democracy. In that case, there is concern that this extension of the term will give rise to a dictatorial leader who rules authoritarianly.